Cilostazol: a Review of Basic Mechanisms and Clinical Uses - Kherallah, Riyad Y.; Khawaja, Muzamil; Olson, Michael; Angiolillo, Dominick; Birnbaum, Yochai (Cardiovascular drugs and therapy, 2022)
Primarily used in the treatment of intermittent claudication, cilostazol is a 2-oxyquinolone derivative that works through the inhibition of phosphodiesterase III and related increases in cyclic adenosine monophosphate (cAMP) levels. However, cilostazol has been implicated in a number of other basic pathways including the inhibition of adenosine reuptake, the inhibition of multidrug resistance protein 4, among others. It has been observed to exhibit antiplatelet, antiproliferative, vasodilatory, and ischemic-reperfusion protective properties. As such, cilostazol has been investigated for clinical use in a variety of settings including intermittent claudication, as an adjunctive for reduction of restenosis after coronary and peripheral endovascular interventions, and in the prevention of secondary stroke, although its widespread implementation for indications other than intermittent claudication has been limited by relatively modest effect sizes and lack of studies in western populations. In this review, we highlight the pleiotropic effects of cilostazol and the evidence for its clinical use.